Intestinal myiasis caused by Clogmia albipunctata in Nepal: a case report - Bimal Sharma Chalise; Saroj Kumar Gupta; Saugat Pradhan; Ajita Khanal; Milan Bajracharya; Yubanidhi Bausla; Shiva Prasad Sharma Chalise (Journal of Medical Case Reports)
Abstract Background Intestinal myiasis is a type of myiasis resulting from the accidental consumption of Clogmia albipunctata larvae. This type of myiasis generally displays symptoms such as nausea, vomiting, abdominal distention and discomfort, loss of appetite, weight loss, and intermittent diarrhea. It is a rare form of myiasis with relatively scarce literature in Nepal. Case presentation We report probably the first case of human intestinal myiasis caused by Clogmia albipunctata in Nepal. A 39-year-old nondiabetic female, Brahmin belonging to khas/arya ethnicity presented with complaints of abdominal discomfort, perianal itching, occasional nausea, and vomiting in the outpatient clinic of Sukraraj Tropical and Infectious Disease Hospital, Teku, Kathmandu. With an additional history of the passing of worms in stool, the sample was examined in the microbiology department, which revealed multiple larvae. Macroscopy followed by microscopic examination through wet mount preparation was performed, leading to the morphological identification of larva of Clogmia albipunctata. Diagnosis of a rare human intestinal myiasis was made, and the patient was advised to take ivermectin. Conclusion Personal hygiene and sanitation, which prevent fly infestation, can help reduce the incidence of the disease.